2020
DOI: 10.3390/ph13070155
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Disorder in the COVID-19 Pandemic: A Systematic Review of Vulnerabilities and Complications

Abstract: As the world endures the coronavirus disease 2019 (COVID-19) pandemic, the conditions of 35 million vulnerable individuals struggling with substance use disorders (SUDs) worldwide have not received sufficient attention for their special health and medical needs. Many of these individuals are complicated by underlying health conditions, such as cardiovascular and lung diseases and undermined immune systems. During the pandemic, access to the healthcare systems and support groups is greatly diminished. Current r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 246 publications
(380 reference statements)
3
77
1
6
Order By: Relevance
“…Pre-existing comorbidities in tobacco users such as cardiovascular diseases, diabetes, respiratory diseases, and hypertension are found to further aggravate the disease manifestations [58][59][60]. Being an important immune modulator, tobacco significantly suppresses the immune system by reducing antibody responses and T-cell proliferation, thereby increasing the susceptibility of tobacco users towards acute viral infections [61]. A population vulnerability analysis done in Europe indicated that elderly people and those with low immunity are at higher risk of developing severe health consequences from COVID-19 [62].…”
Section: Tobacco Use In the Vulnerable Population Including Adolescentsmentioning
confidence: 99%
“…Pre-existing comorbidities in tobacco users such as cardiovascular diseases, diabetes, respiratory diseases, and hypertension are found to further aggravate the disease manifestations [58][59][60]. Being an important immune modulator, tobacco significantly suppresses the immune system by reducing antibody responses and T-cell proliferation, thereby increasing the susceptibility of tobacco users towards acute viral infections [61]. A population vulnerability analysis done in Europe indicated that elderly people and those with low immunity are at higher risk of developing severe health consequences from COVID-19 [62].…”
Section: Tobacco Use In the Vulnerable Population Including Adolescentsmentioning
confidence: 99%
“…Substance abuse was a risk factor for COVID-19 severity in the current study, which can be the result of direct damage to the respiratory system, modulating brain and immune functions (19). Severe disease was also associated with travel to high-risk areas.…”
Section: Discussionmentioning
confidence: 52%
“…Substance abuse was a risk factor for COVID-19 severity in the current study, resulting from direct damage to the respiratory system, modulating brain, and immune functions (19). Severe disease was also associated with travel to high-risk areas.…”
Section: Discussionmentioning
confidence: 55%